2014
DOI: 10.1542/peds.2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Shock Syndrome Complicating a Recurrence of Kawasaki Disease

Abstract: We describe a case of recurrent Kawasaki disease (KD) in a non-Asian 6-year-old boy who had been diagnosed with typical KD without cardiac involvement at age 3 years. He was admitted to the PICU 3 years later for heart failure, hypotension, and deterioration of his general condition. Ultrasonography revealed left ventricular dysfunction with a 44% ejection fraction and grade I mitral valve failure without coronary artery involvement. Subsequent observation of hyperemic conjunctiva, bilateral cervical adenopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
(27 reference statements)
0
12
1
5
Order By: Relevance
“…The most frequent diagnosis at the time of admission was TSS or septic shock. Twenty patients were diagnosed with TSS, 16 of whom had coronary artery abnormalities . Other common diagnoses were suppurative lymphadenitis and myocarditis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent diagnosis at the time of admission was TSS or septic shock. Twenty patients were diagnosed with TSS, 16 of whom had coronary artery abnormalities . Other common diagnoses were suppurative lymphadenitis and myocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty patients were diagnosed with TSS, 16 of whom had coronary artery abnormalities. 5,7,9,17,[19][20][21][22][23]26,33,34,39 Other common diagnoses were suppurative lymphadenitis and myocarditis. Seventy-two patients had complete KD (69.9%), and 31 had incomplete KD (31.1%).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis is usually made on a constellation of characteristic clinical findings, which may appear sequentially 1. KD is a serious and potentially life-threatening condition 2. It results in coronary artery aneurysms in up to a quarter of untreated patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most studies, including in our two patients, in acute KDSS, lower platelet counts were more common . Given these considerations, it is very important to make a correct diagnosis using echocardiography to detect coronary artery lesions and to give appropriate treatment . In our two patients, we also found that serum BNP or N‐terminal proBNP (NT‐proBNP) might play an important role in differentiating KDSS from TSS, each of these values increased during hypotension.…”
Section: Discussionmentioning
confidence: 55%
“…Lin, et al stated that, echocardiographic abnormities, especially coronary artery lesions, anemia, and thrombocytosis were highly suggestive of KDSS . However, in most studies, including in our two patients, in acute KDSS, lower platelet counts were more common . Given these considerations, it is very important to make a correct diagnosis using echocardiography to detect coronary artery lesions and to give appropriate treatment .…”
Section: Discussionmentioning
confidence: 64%